How can academic health science centers help to increase diversity in the STEM professions? - Moore, Mary; Cuccia, Martha; Edwards, Alicia; Hicks, Chindo; McLean, Angela; Nieves-Rivera, Christian; Sheets, Gabrielle; Sherman, Kelly Jean; Augustus-Wallace, Allison; Tsien, Fern (Frontiers in Education, 2024)
In the United States, great inequities exist within the science, technology, engineering, and math (STEM) fields in individuals who self-identify as belonging to underrepresented groups (e.g., from socioeconomically disadvantaged backgrounds, people with disabilities, and Black/African American, Hispanic/Latino, American Indian, Alaska Native, Native Hawaiian, or Pacific Islander). Underrepresentation in STEM careers has been documented to be due to a lack of qualified and diverse teaching personnel, limited access to resources in disadvantaged schools, and implicit bias within US institutions. In recognition of these inequities, an interprofessional team of biomedical faculty members and diversity, equity and inclusion (DEI) educators from the Louisiana State University Health Science Center (LSUHSC) in New Orleans developed and implemented a STEM educational training pipeline for elementary, middle, and high school (K-12), undergraduate, and medical students, with accompanying DEI training for LSUHSC mentors and staff to mitigate implicit bias and promote a welcoming environment for participants from different backgrounds. Our findings focus on one social determinant of health: access and quality of education. Other institutions can implement a program as described in the present study to address the educational and health inequities in their own communities.